Synthesis of Ni/SBA-15 For CO2 Reforming of CH4: Utilization Of Palm Oil Fuel Ash As Silica Source - Nornasuha, Abdullah; C. C., Chong; N. Aini, Razali; Chin, S. Y.; Setiabudi, H. D. (2017)
In this study, Ni/SBA-15 was synthesized using Palm Oil Fuel Ash (POFA) as the silica source and was applied in the CO2 reforming of CH4 (CRM). The preparation of POFA sodium silicate (POFA-Na2SiO3) was carried using sodium hydroxide (NaOH) fusion method under several parameters including NaOH/POFA mass ratio, fusion temperature and NaOHfused POFA/H2O mass ratio. The optimum condition was achieved at NaOH/POFA mass ratio of 2:1, fusion temperature of 550 oC and NaOH-fused POFA/H2O mass ratio of 1:4, with maximum silica content of 40570 ppm. POFA-Na2SiO3 was used as the silica source for the synthesis of Ni/SBA-15(POFA), and its properties and catalytic performance were compared with Ni/SBA-15(TEOS). The physicochemical properties of the catalysts were characterized using XRD, BET and FTIR, meanwhile the catalytic performance of the catalyst was carried out in a fixed bed reactor at 800°C, atmospheric pressure and CO2/CH4 feed ratio of 1/1. The characterization results revealed that the physicohemical properties of Ni/SBA-15(POFA) were comparable with Ni/SBA-15(TEOS), except for the size of Ni and the strength of metalsupport interaction. The catalytic performance results showed that Ni/SBA-15(POFA) has comparable CO2 conversion (around 82%), but lower in CH4 conversion (differences around 27%) and stability, which might be due to the larger Ni size and weak metal-support interaction in Ni/SBA-15(POFA) as compared to Ni/SBA-15(TEOS). Although Ni/SBA-15(POFA) showed lower CH4 conversion in CRM, POFA can be considered as an alternative silica source to synthesis Ni/SBA-15 owing to the fact that the deficiency observed in the present catalyst can be improved via metal loading method.